Honey resources directory available - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
'Directory of Important World Honey Sources' database Information Officer for Tropical Apiculture - IBRA - 18 North Road - Cardiff CF1 3DY- UK